2012
DOI: 10.1519/jsc.0b013e31824e16fe
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pitch Counts and Days of Rest on Performance Among Major-League Baseball Pitchers

Abstract: Although the belief that overuse can harm pitchers is widespread, there exists little evidence to show that the number of pitches thrown and the days of rest affect future performance and injury among adults. The purpose of this study is to quantify the effects of pitches thrown and the days of rest on pitcher performance. We examined performances of major-league baseball starting pitchers from 1988 to 2009 using fractional polynomial multiple regression to estimate the immediate and cumulative impact of pitch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 10 publications
0
36
0
Order By: Relevance
“…Studies have shown that higher pitch count in a pitcher can lower future performance levels, with each pitch averaged in the preceding 5 and 10 games increasing the ERA by 0.014 and 0.022, respectively. 15 However, no studies have found a correlation between pitch count and risk of future injuries. The disadvantages of different types of pitches, such as fastball versus curveball, have also been extensively studied but no general consensus regarding the possible association between pitch count and future injuries has been reached.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that higher pitch count in a pitcher can lower future performance levels, with each pitch averaged in the preceding 5 and 10 games increasing the ERA by 0.014 and 0.022, respectively. 15 However, no studies have found a correlation between pitch count and risk of future injuries. The disadvantages of different types of pitches, such as fastball versus curveball, have also been extensively studied but no general consensus regarding the possible association between pitch count and future injuries has been reached.…”
Section: Discussionmentioning
confidence: 99%
“…The repetitive microtrauma induced from throwing over a career (~3000 to 5000 innings pitched in competition 11 ) may lead to several osseous and soft tissue adaptations, both functional and pathologic. This has led to a reduction in allowed pitch counts in both MLB 1,30 and youth baseball 27,30 in attempts to reduce injury 30,38 and improve performance. 1 The inability to throw, in context of the sudden loss of ability to pitch (“the dead arm”), “is nothing short of an athletic tragedy.” 32,41 The latter may occur in as little as 1 pitch to as much as several years.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to a reduction in allowed pitch counts in both MLB 1,30 and youth baseball 27,30 in attempts to reduce injury 30,38 and improve performance. 1 The inability to throw, in context of the sudden loss of ability to pitch (“the dead arm”), “is nothing short of an athletic tragedy.” 32,41 The latter may occur in as little as 1 pitch to as much as several years. Accordingly, treatment often takes place over several months to years, with many different nonoperative and operative options utilized.…”
Section: Discussionmentioning
confidence: 99%
“…I test whether the people managing Major League Baseball (MLB) teams exhibit left digit bias when making decisions regarding player substitutions. Bench managers and upper management must weigh performance, fatigue, and injury risk when faced with such decisions (Tango, Lichtman, and Dolphin ; Bradbury and Forman ). I find that experienced decision makers respond to these tradeoffs in a manner indicating the salience of round numbers.…”
Section: Introductionmentioning
confidence: 99%